Remoção de matéria carbonácea, nitrogenada e fosfatada em um sistema anaeróbio-aeróbio-anóxico (AOA) submetido a variações de cargas orgânicas e hidráulicas - Ferro, Thayse Nathalie (2018)
In Brazil, sewage treatment plants have their configurations based on anaerobic processes followed or not by post-treatment, usually aerobic. These configurations have limitations such as low nutrient removal efficiency. Thus, when considering technical aspects, it was intended to evaluate the efficiency of removal of carbonaceous, nitrogenous and phosphate in an anaerobic (22.1 L), aerobic (19.9 L) and anoxic (17.4 L) (AOA) treating synthetic wastewater. Polyvinyl chloride corrugated rings (PVC) were used as support material for biomass fixation. The behavior of the system was evaluated in four different stages in order to analyze the influence of the addition of carbon in the anoxic reactor and the reduction of Hydraulic Retention Times (θh) in the anaerobic and aerobic reactors. The performance of the system was studied by means of temporal sampling profiles with determination of the physicchemical parameters temperature, pH, alkalinity total (AT) and bicarbonate (AB), volatile acids (VA), dissolved oxygen (OD), oxidation potential (REDOX), turbidity (UNT), chemical oxygen demand (COD), total nitrogen kjeldahl (NTK), ammoniac nitrogen (N-NH4 + ), nitrite (N-NO2 - ), nitrate (N-NO3 - ), and total phosphorus (P-PO4 -3 ) in samples of the influent and effluent from each reactor collected at intervals of 3 h for 24 h. In Stage 1, the removal efficiency of 97%, 57% and 50% of carbonaceous, nitrogenous and phosphate matter was obtained for the system operated with θh of 8 h for the anaerobic reactor, 7.3 h for the aerobic reactor and 6.4 h for the anoxic reactor. In Stage 2 with the addition of 20% of the raw sewage inflow (carbon source) and maintenance of the θh values, the carbon and total nitrogen removal efficiencies were 95% and 55%, with no reported removal efficiency phosphor. In Stage 3, with the removal of the carbon source and reduction of the θh in the anaerobic and aerobic reactors for 4 h, removal efficiencies of 96% of carbonaceous matter, 51% of total nitrogen and 40% of phosphorus were obtained. In Stage 4 with the maintenance of the θh of 4 h for the anaerobic reactor, 7.3 h for the aerobic reactor and 6.4 h for the anoxic reactor, the removal efficiencies resulted in 97% of carbonaceous matter, 43% of total nitrogen and 41% phosphorus. With the kinetic study, it was possible to verify that the reduction of the C/N positively influenced the performance of the nitrifying and denitrifying microorganisms. Finally, it can be concluded that the AOA system presented removal efficiency of carbonaceous matter higher than the limit required by the legislation and provided simultaneous removal of nitrogen and phosphorus.